Effect of MnO on the electrical properties of Nb-doped SrTiO3 varistor - Kim, SH; Seon, HW; Kim, Y (SOLID-STATE CHEMISTRY OF INORGANIC MATERIALS II, 1999)
The effect of MnO on the electrical properties of Nb-doped SrTiO3 was investigated to understand the electronic states of grains and grain boundaries. Grain size and dielectric constant were decreased with increasing Mn-doped content from 0 to 0.07 mol%. However, it was observed that the non-linearity coefficient of Nb-doped SrTiO3 was changed from 5 to 43 with Mn-doped content increasing from 0 to 0.03 mol%. Current-voltage (I-V) characteristics, capacitance-voltage (C-V) measurement, complex plane analysis and impedance spectroscopy were performed to obtain the information about the electrical properties of grains and grain boundaries. The potential barrier height increased and the donor concentration decreased with increasing Mn-doped content. This phenomena, that the electrical properties of Nb-doped SrTiO3 were changed with the addition of Mn, would be determined by the effect which Mn+2/+3 substituted for Ti sites. It was observed that the breakdown voltage of single grain boundary was changed from 3.8 V to 8.9 V when measured by micro-electrode method.